Parameters for the depth of the ocean’s productive layer - Marra, John F.; Chamberlin, W. Sean; Knudson, Carol A.; Rhea, W. Joseph; Ho, Cheng (Frontiers in Marine Science, 2023)
Here we compare various parameters that are used to define the depth of the ocean’s productive layer, the euphotic zone, during the initiation of the spring phytoplankton bloom in the North Atlantic (47°N/20°W). These are (1) the compensation depth (Zc, where gross photosynthesis balances autotrophic respiration), (2) the depth horizon of 1% of surface photosynthetic active irradiance (Ed(0-,PAR), (3) depth horizon of 1% of surface Ed(488), and (4) the depth of the bottom of the fluorescence maximum. We also use two related parameters, the depth of the mixed layer and the ratio of integral gross production to integral respiration as a scaling factor for a proxy for the critical depth. Over the course of the observational period (25 April - 7 May, 1989), the mixed layer decreased from 162 to 20 m, and Zc decreased from 64 to 35 m. The depth of 1%Ed(0-,PAR) followed the trajectory of Zc, while Ed(488) and the depth of the bottom of the fluorescence maximum were about 10 m deeper, on average. These data support the criterion of the depth of “1%PAR” to describe the productive layer for more productive areas of the ocean. However, 1% of Ed(488) or the bottom of the fluorescence maximum could be used over a broader range of trophic conditions.